Anti-oxidant components from the aerial parts of Asterothamnus centrali-asiaticus. (September 2016) - Wang, Yan-Ming; Zhao, Jian-Qiang; Yang, Chun-Yan; Tao, Yan-Duo; Mei, Li-Juan; Shi, Yan-Ping
Graphical abstract: Highlights: ⿢ Two new phenolic acids (1 ⿿2 ) were isolated from the aerial parts of Asterothamnus centrali-asiaticus . ⿢ Five knownphenolic acids (3 ⿿7 ) were also obtained from the title plant. ⿢ 1 ⿿7 were evaluated for their anti-oxidant activity. ⿢ 1 ⿿7 showed anti-oxidant activity with IC50 values ranging from 7.65 to 22.44 μg/mL. Abstract: Two new phenolic acids 2-hydroxy-5-[(6⿲- O -( E )-caffeoyl)-β-d -glucopyranosyl]-oxybenzoic acid (1 ) and 2-hydroxy-5-[(3⿲- O -( E )-caffeoyl)-β-d -glucopyranosyl]-oxybenzoic acid (2 ) were isolated from the aerial parts of Asterothamnus centrali-asiaticus, together with five known ones (3 -7 ). Their structures were elucidated by extensive 1D and 2D NMR studies and HRESIMS investigations. The anti-oxidant activity of the isolates was evaluated through ABTS radical cation decolorization assay. The results showed that all of them exhibited anti-oxidant activity, and compound7 was the most active compound with an IC50 value of 7.65 μg/mL.